“Open the doors to other worlds”: The UNESCO Fellowship and Travel Grants abroad and educational modernization in Spain (1953-1975) - González-Delgado, Mariano; Groves, Tamar (Historia y Memoria de la Educación, 2024)
This research analyzes the development of the UNESCO fellowship program and Travel Grants in Spain and its relationship with the processes of educational modernization during the Franco dictatorship and the first years of democracy. The paper begins with a brief overview of the importance, from a theoretical point of view, of studying scholarship programs to understand the processes of transfer and configuration of educational discourses. From here, this research examines in depth the deployment of the program in Spain. The number of fellowships awarded by UNESCO is studied, as well as the topics or lines of research worked on and the countries that were visited by the beneficiaries. The last part of the article provides a summary approximation to the impact that the fellowships could have on the configuration of the field of Pedagogy during the Franco regime and the first years of the Transition. The article concludes that the fellowship and travel grants program underwent a process of change due to the importance that the Modernization Theory acquired within International Organizations with regard to the defining of educational policies during this period. On the other hand, it indicates the importance that the UNESCO program played as a significant factor in the processes of transfer and configuration of a new educational discourse or international narrative known as global educational governance or global architecture of education.